Draft Environmental Impact Report/Environmental Assessment for Oxnard Airport Master Plan Notice of Availability - Kari Gialketsis:::::: (1998)
A notice notifying the members of the Board of Supervisors that the Environmental Report Review Committee is holding a meeting reviewing the environmental report regarding the Oxnard Airport.